As fotografias de André Bello (1879-1941): imagens da modernidade em São João Del Rei - Rubia Soraya Lelis Ribeiro (2006)
The aim of this dissertation about Social History of Culture is to approach the presence of photography, a sign of modernity, in a city of the state of Minas Gerais in Brazil. The specifications of the insertion of São João Del Rei, a city with a strong colonial tradition, are analysed in some speeches about progress and modernity, having André Bellos photographs (1879 1941) as the photograph representations of the city and its inhabitants. For this purpose, the dialogs that he had in his speeches with the modernity and progress, with the universe of photography, and with the speeches about São João Del Rei, produced by academic dissertation authors and chroniclers of local periods, are considered in this piece of work. In this context, the photography appears as a symbol of a kind of modernity that embodies either the signs of material progress and the signs that connect the city and its inhabitants to their ancient colonial times.